Material selection and design analysis of multi-purpose disposable safety syringe - Nasri Ishak, Mohd; Rahim Abu Talib, Abd; Yazdi Harmin, Mohammad (International Journal of Engineering and Technology, 2018)
Current design of safety syringes requires two handed operation and additional processes which is not similar to the normal syringes. Due to this concern, a new design of safety syringe is introduced in order to produce a safety syringe which allows a single-handed operation and similar to the operation of a normal syringes. This paper presents the material selection process and design analysis of a newly devel-oped multi-purpose disposable safety syringe. Based on the design analysis, the force which needed to dismantle the nozzle is found to be 20 N and this value is practical for the end users. The finite element analysis had also shown that the design concept is safe and has safety feature for the user to use. In addition, copolymer is proven as the best material selection for safety syringe production.